Numerical Investigation on the Effect of Composite Corrugated Cores in Lightweight Sandwich Panels under Planar Impact Loading - Jamal-Omidi, Majid; Zabihpoor, Mahmood; Vaezi, Mehdi; Choopanian Benis, Ali (International Journal of Integrated Engineering, 2022)
Lightweight sandwich structural components have been widely used in different industries as highly effective energy absorbers. This research aims to provide a comparative study on the role of the composite corrugated sheet as a core in sandwich panels under low velocity impact loading. To reach this goal, the crashworthiness characteristics of three sandwich panels with different corrugated cores, which consist of identical mass and mechanical properties, are evaluated under vertical and transverse loading. The finite element computation is done using LS-DYNA under planar loading conditions. To validate the numerical process, first, the dynamic compression behavior of the square corrugated core sandwich panel made of aluminum alloys in comparison to existing experimental data is analyzed and the appropriate compliance has been observed. Then the effect of composite material and core shape on the crashworthy behavior of sandwich panels is explored. The research results reveal that the material type and geometric configuration of corrugated core have a considerable effect on the mean crushing load and the energy absorption of sandwich panels. It is found that the triangular configuration has a higher capability in load carrying and energy absorption than the square and/or the sinusoidal configuration. The failure modes of the crushed corrugated sandwich panels also significantly influenced by the type of corrugation cores. The present results supply valuable information on low velocity impact response that can be helpful for increasing crashworthy performance and development of such lightweight structures.